The neural milieu of the developing choroid plexus: neural stem cells, neurons and innervation - Prasongchean, Weerapong; Vernay, Bertrand; Asgarian, Zeinab; Jannatul, Nahin; Ferretti, Patrizia (Frontiers in Neuroscience, 2015)
The choroid plexus (CP) produces cerebrospinal fluid and plays an important role in brain homeostasis both pre and postnatally. In vitro studies have suggested that cells from adult CPs have stem/progenitor cell-like properties. Our initial aim was to investigate whether such a cell population is present in vivo during development of the CP, focusing mainly on the chick CP. Cells expressing neural markers were indeed present in the CP of chick and also those of rodent and human embryos, both within their epithelium and mesenchyme. ß3-tubulin-positive cells with neuronal morphology could be detected as early as at E8 in chick CPs and their morphological complexity increased with development. Whole mount immunochemistry demonstrated the presence of neurones throughout CP development and they appeared to be mainly catecholaminergic, as indicated by tyrosine-hydroxylase reactivity. The presence of cells co-labelling for BrdU and the neuroblast marker, doublecortin, in organotypic CP cultures supported the hypothesis that neurogenesis can occur from neural precursors within the developing CP. Furthermore, we found that extrinsic innervation is present in the developing CP, unlike previously suggested. Altogether, our data are consistent with the presence of neural progenitors within the CP, suggest that at least some of the CP neurones are born locally, and show for the first time that CP innervation occurs prenatally. Hence, we propose the existence of a complex neural regulatory network within the developing CP that may play a crucial role in modulating its function during development as well as throughout life.